Isolation and molecular identification of Philippine symbiotic bioluminescent bacteria from fish hosts and screening of their crude extracts against nosocomial bacteria - ANALIZA, MOLINA (Archīum Ateneo, 2014)
Bioluminescent bacteria (BLB) are the most abundant light-emitting organisms on earth. Though the Philippines is endowed with immense biodiversity in its vast marine ecosystems, BLB remain unidentified and untapped for potential biotechnological applicati